2011
DOI: 10.1007/s10948-011-1296-0
|View full text |Cite
|
Sign up to set email alerts
|

Ion Beam Analysis and Normal-State Conduction Mechanisms for (Bi, Pb)-2223 and (Tl, Pb)/Sr-1212 Superconducting Phases Substituted by Ruthenium

Abstract: Superconducting samples of type Bi 1.8 Pb 0.4 Sr 2 Ca 2.1 Cu 3−x Ru x O 10+δ , (Bi, Pb)-2223, with 0.0 ≤ x ≤ 0.4 and type Tl 0.5 Pb 0.5 Sr 1.6 Ba 0.4 CaCu 2−x Ru x O 7−δ , (Tl, Pb)/ Sr-1212, with 0.0 ≤ x ≤ 0.525 were synthesized using the standard solid-state reaction technique. The lattice parameters and the surface morphology for these samples were determined using X-ray powder diffraction (XRD) and scanning electron microscope (SEM) measurements, respectively. All element-contents of the samples prepared we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Much literature has been published by our group for studying PIXE and RBS of Cu 0. 25 [23]. These studies found that the real stoichiometry, as weight %, obtained from PIXE spectra was very close to the starting values.…”
Section: Introductionsupporting
confidence: 67%
“…Much literature has been published by our group for studying PIXE and RBS of Cu 0. 25 [23]. These studies found that the real stoichiometry, as weight %, obtained from PIXE spectra was very close to the starting values.…”
Section: Introductionsupporting
confidence: 67%